Ulu al-Albab in the Qur'an: Meaning, Characteristics, and Role in Social Change - Zaini, Muhammad (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan Pusat Jurnal Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study aims to examine the Qur'anic verses that mention